The Effectiveness of International Commercial Arbitration in Federal Iraq: A Critical Study - Talib, Nizam Jabbar; Jaiz, Ali Abdul-Sada (Journal of Legal and Political Studies, 2025)
International commercial arbitration stands as an effective legal mechanism for resolving cross-border commercial disputes, widely recognized for its procedural flexibility and confidentiality, making it a strategic choice for enhancing trust in investment environments. Despite Iraq’s accession to the 1958 New York Convention (aimed at facilitating the recognition and enforcement of foreign arbitral awards), the country continues to face substantial legislative challenges that hinder the activation of this mechanism, particularly due to the absence of a comprehensive national law regulating international commercial arbitration. This legislative gap threatens Iraq’s appeal as a destination for foreign investments. The core issue arises from the conflict between Iraq’s international obligations under ratified conventions and its reluctance to translate these obligations into domestic legislation that governs arbitration procedures and ensures the enforcement of awards. The current Iraqi legal system relies on fragmented provisions in laws such as Investment Law No. 13 of 2006, which permits arbitration without establishing a clear framework for its mechanisms. This ambiguity is exacerbated by Iraq’s federal structure, which demands precise coordination between federal legislation and the laws of the Kurdistan Region. The study highlights that the lack of legislative clarity intensifies conflicts between the central government and the Kurdistan Region, particularly in disputes related to the oil and investment sectors, where the Kurdistan Regional Government occasionally adopts independent policies conflicting with federal laws. In this context, international arbitration presents an opportunity to strengthen legal unity through neutral mechanisms capable of efficiently resolving both internal and external disputes. It also enhances investor confidence by offering guarantees of impartiality and confidentiality—advantages absent in traditional judicial procedures, which are often slow and complex. In conclusion, the study emphasizes that improving the efficacy of international commercial arbitration in Iraq requires urgent legislative reform, including the enactment of a specialized law aligned with international standards, such as the UNCITRAL Model Law (1985), and the establishment of independent national arbitration bodies to coordinate efforts between the federal government and the Kurdistan Region. These steps are not merely legal necessities but also a strategic investment in strengthening Iraq’s economic standing and ensuring its active integration into the global trade system. Keywords: International Commercial Arbitration in Iraq, Domestic Conflict of Laws, New York Convention 1958, UNCITRAL Rules, Enforcement of Arbitral Awards
Keywords: International Commercial Arbitration in Iraq; Domestic Conflict of Laws; New York Convention 1958; UNCITRAL Rules; Enforcement of Arbitral Awards